The Relative and Absolute Chronology of the Cypriote White Painted Pendent Line Style - Merrillees, Robert S. (Bulletin of ASOR, 2002)
The occurrence abroad of Cypriote ceramics decorated in the later White Painted tradition, especially in historically dated contexts in Egypt, Syria, and Anatolia, has the potential to further refine the absolute chronology of the island's Middle and Late Bronze Ages. Taken in conjunction with the finds of White Slip, Base-ring, and Bichrome Wheel-made pottery, which have recently been the theme of separate conference proceedings, the exports of White Painted Pendent Line Style to the Levant make it possible to postulate that this ware, which overlapped with Middle Cypriote III and Late Cypriote IA, spanned 1700 to 1550 B. C. in absolute terms. On this basis it has been argued that Middle Cypriote III lasted from 1750 to 1650 B. C., and Late Cypriote IA from 1650 to 1550 B. C.